Physiological Responses and Nonspecific Immunity in Striped Catfish (Pangasianodon hypophthalmus) Fed Fermented Herbal Medicine - Wiwik Yuliana; Henni Syawal; Morina Riauwaty; Fahrurrozi Fahrurrozi (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Aeromonas hydrophila infections in aquaculture can cause mass mortality of up to 80–100% of striped catfish. Adding fermented herbal medicine containing essential oils, curcumin, flavonoids, and xanthorrhizol to feed can boost the fish's immunity. This study aims to analyze the optimal frequency of administering fermented herbal supplements in feed to enhance fish immunity, conducted from June 2024 to June 2025. A Completely Randomized Design (CRD) was used with 5 treatments and 3 replicates: Kn (no supplement, no infection), Kp (no supplement, infected with A. hydrophila), with 200 mL/kg of herbal supplement administered daily (P1), once every 3 days (P2), and once every 5 days (P3). The fish (P. hypophthalmus fingerlings, 8–12 cm, 20 fish/tank) were reared in 100-liter plastic buckets for 46 days. On day 32, the fish were infected with A. hydrophila (intramuscularly, 0.1 mL, 10⁸ CFU/mL), and they were maintained for 14 days thereafter. Each container was equipped with an aerator and a Dacron filter. The best results were obtained in P1, which showed a survival rate (SR) of 100%, a post-infection survival rate of 100%, a weight gain of 109.33 ± 2.51 g, serum protein of 3.94 ± 0.06 g/dL, albumin 3.76 ± 0.05 g/dL, globulin 0.21 ± 0.04 g/dL, lysozyme activity 373.33 ± 15.27 U/mL, and phagocytosis activity 51.11 ± 16.44%. Based on the data obtained, it can be concluded that the daily administration of 200 mL/kg of fermented herbal supplement in the diet yields the best results in enhancing the immune response and growth of P. hypophthalmus infected with A. hydrophila.